The role of Interventional Radiology in primary and metastatic liver disease – a short review of primary methods and therapy approaches - Ciaś, Marek; Mruk, Bartłomiej (Wiedza Medyczna, 2021)
Primary and metastatic liver tumors are an increasing global health burden. As of 2020 colorectal cancer (CRC), which often presents with hepatic metastasis in the course of the disease was a second leading cause of cancer-related mortality worldwide. This was followed by hepatic cell carcinoma (HCC). Besides systemic therapies and surgical methods, which are not always applicable, many locoregional approaches were developed and are being increasingly implemented in the field of interventional radiology (IR) – both as primary and bridging procedures. The purpose of this article is to outline and briefly discuss these primary approaches used in IR in liver neoplastic disease.